What we think we know and what we want to know: perspectives on trust in news in a changing world - Toff, B; Badrinathan, S; Montalverne, C; Rossarguedas, A; Fletcher, R; Nielsen, R (Reuters Institute for the Study of Journalism, 2020)
This report summarises some of what is known and unknown about trust in news, what is contributing to changing attitudes about news worldwide, and how media organisations are responding to increased digital competition. The report combines an extensive review of existing research on the subject along with findings from 82 in-depth interviews with journalists and other practitioners across Brazil, India, the United Kingdom, and the United States – four countries with varying media and political systems. The report argues that there is no single ‘trust in news’ problem but rather multiple challenges involving both the supply of news and the public’s demand for information. Empirical evidence about what works, with whom, and under what circumstances, remains lacking, especially around the role played by platform companies. The report emphasises the need to grapple with trade-offs. Some efforts to regain or retain trust in accurate and reliable news are likely to alienate some audiences over others.